THE INFLUENCE OF CONSUMER’S PERCEPTION ON SERIAL ADVERTISEMENT TOWARD THEIR ATTITUDE AND PURCHASE INTENTION (AN EXPERIMENTAL STUDY OF PONDS COSMETIC PRODUCT) - Ana Bella Parina; Suci Paramitasari Sahlani; Achmad Fudholi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
To attract consumer a company should make creative advertisement. One of them is conducted through the useof serial-drama-based advertisement as implemented in the Ponds’ cosmetics product advertisement. This researchaimed to identify whether consumer perception on the serial advertisements of Ponds’ cosmetic products providedsignificant influences on consumer attitude and purchase intention, and to compare consumer perception on theconsumer attitude towards serial advertising and consumer perception on the consumer attitude toward non serial advertising. In this research, the effects of consumer perception on the consumer attitude and consumer purchaseintention towards Ponds’ cosmetics products were measured.This was an experimental research with participants divided into 2 groups, namely, participant group treated with serial advertisement, and participant group treated with non serial-advertisement. Research instruments involved advertisement video samples of Ponds’ cosmetics and research questionnaires. Total samples were 60 persons in eachgroup of serial advertisement and non serial-advertisement. Data obtained were analyzed using simple regressionand significance test through the use of SPSS 17 for Windows. Based on the regression analysis, it was showed that the significant effects of consumer perception on the consumer attitude toward serial advertisement on t-test 8,205, the significant effects of consumer perception on serialadvertisement towards consumer purchasing intention on t-test 8,797, and the significant effects of consumer attitudeon the serial advertisement toward consumer purchasing intention on t-test 6,274. After comparison between theeffects of consumer perception on consumer attitude towards serial advertisement, and the effects of the effects ofconsumer perception on the consumer attitude on non-serial advertisement using t-test it was indicated that theeffects of consumer perception on the consumer attitude toward serial advertisement was higher than the consumer perception towards the consumer attitude on non-serial advertisement. Keywords: advertisement, serial-advertisement, consumer perception, consumer attitude, consumer purchaseintention, t-test.